2022
DOI: 10.1016/j.jhepr.2021.100391
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory receptor VSIG4 is released during spontaneous bacterial peritonitis and predicts short-term mortality

Abstract: Background & Aims V-set Ig-domain-containing 4 (VSIG4) is an immunomodulatory macrophage complement receptor modulating innate and adaptive immunity and affecting the resolution of bacterial infections. Given its expression on peritoneal macrophages (PMs), we hypothesised a prognostic role of peritoneal VSIG4 concentrations in patients with spontaneous bacterial peritonitis (SBP). Methods We isolated PMs from patients with cirrhosis and analysed VSIG4 expression and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(92 reference statements)
1
1
0
Order By: Relevance
“… 41 Higher peritoneal VSIG4 levels can be used to predict the prognosis of spontaneous bacterial peritonitis, while regulating the ratio of VSIG4-expressing macrophage subpopulations might provide new therapies for cirrhosis and ascites. 42 , 43 Our results showed that the VSIG4 expression level was significantly correlated with T-cell activation/differentiation and inflammatory response-related bioprocesses and positively associated with WBC, INR and neutrophil levels in patients with HBV-ACLF, which is consistent with the findings of previous studies, indicating that the potential function of VSIG4 may be to correct immune disorders during ACLF progression. VSIG4 is tightly linked with serum urea levels, which might alleviate acute kidney injury by suppressing inflammation.…”
Section: Discussionsupporting
confidence: 91%
“… 41 Higher peritoneal VSIG4 levels can be used to predict the prognosis of spontaneous bacterial peritonitis, while regulating the ratio of VSIG4-expressing macrophage subpopulations might provide new therapies for cirrhosis and ascites. 42 , 43 Our results showed that the VSIG4 expression level was significantly correlated with T-cell activation/differentiation and inflammatory response-related bioprocesses and positively associated with WBC, INR and neutrophil levels in patients with HBV-ACLF, which is consistent with the findings of previous studies, indicating that the potential function of VSIG4 may be to correct immune disorders during ACLF progression. VSIG4 is tightly linked with serum urea levels, which might alleviate acute kidney injury by suppressing inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, peritoneal macrophages shed VSIG4 during SBP, and the level of soluble VSIG4 in ascites is correlated with disease severity and mortality from SBP. However, soluble VSIG4 does not directly affect peritoneal macrophage lipopolysaccharide (LPS)-induced TNF-α release or phagocytic activity [26]. Other groups have found that during SBP episodes, LPMs change to a more inflammatory phenotype characterised by low CD206, low MER Proto-Oncogne Tyrosine Kinase (MERTK) and normal CD163 cell surface expression.…”
Section: Macrophagesmentioning
confidence: 99%